ANALISIS VARIANS MULTIVARIAT TERHADAP RETURN DAN RISIKO PORTOFOLIO YANG DITENTUKAN DENGAN ELTON GRUEBER PADBERG MODEL PADA EMPAT KELOMPOK INDEKS (LQ 45, SRI-KEHATI, JII, DAN ISSI) - Baiq Nurul Suryawati (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2016)
AbstractThis research emphasizes the difference between risk and return on four group of index, which are LQ 45, SRI KEHATI, JII and ISSI. Test of significance conduct by doing Analysis of Varians Multivariate. The Analysis of Varians Multivariate results more accurate than repeatedly t-test among group. EGP Model mostly explained as Single Index Model in various textbook. Thus, Single Index Model only clarified influence of a Single Market Index for Individual Index, EGP Model use Reward to Volatility (RVOL) for measuring excess return to systematic risk. The results shows that after 15 years from sharia index introduce in Indonesian Stock Exchange, it shows significant difference between sharia index and conventional stock market. However, LQ 45 shows it persistence as high return high risk index consistently. The Analysis VariansMultivariate also shows SRI KEHATI, as an ethic businesses representative in Indonesian Stock Exchange as a weaker index. SRI KEHATI shows that various group portfolio form by EGP Model could not exceed JII performance. Therefore, it concludes that indexes provide by capital market to facilitise the preference of investor whereas,it is tremendously various. To invest in stock market, investor need to clarify their wants and needs. Whether their wants is to gain more return or to accommodate their risk, and their preferrence to invest in various kind of business or certain business such as business based on ethic or faith.Keywords: Analysis of Varians Multivariate; Risk and Return; EGP Model; Indexes; LQ 45; Sri-Kehati; Jakarta Islamic Index (JII); and Indeks Saham Syariah Indonesia (ISSI)